2021
DOI: 10.6061/clinics/2021/e2284
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction targeting 16S ribosomal RNA for the diagnosis of bacterial meningitis after neurosurgery

Abstract: OBJECTIVES: Bacterial and aseptic meningitis after neurosurgery can present similar clinical signs and symptoms. The aims of this study were to develop and test a molecular method to diagnose bacterial meningitis (BM) after neurosurgery. METHODS: A 16S ribosomal RNA gene PCR-based strategy was developed using artificially inoculated cerebrospinal fluid (CSF) followed by sequencing. The method was tested using CSF samples from 43 patients who had undergone neurosurgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our study demonstrated the potential of 16S rRNA gene PCR/sequencing (30% of tested, culture negative CSF samples were positive) that can identify the presence of bacteria even in patients who have already received antibiotics [ 14 , 15 , 16 ]. This method can also provide more rapid identification, especially of slow-growing and fastidious bacteria [ 17 , 18 ]. Multiple studies on broad range PCR methods in HCAMV report high specificity and often limited sensitivity [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated the potential of 16S rRNA gene PCR/sequencing (30% of tested, culture negative CSF samples were positive) that can identify the presence of bacteria even in patients who have already received antibiotics [ 14 , 15 , 16 ]. This method can also provide more rapid identification, especially of slow-growing and fastidious bacteria [ 17 , 18 ]. Multiple studies on broad range PCR methods in HCAMV report high specificity and often limited sensitivity [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, culture is frequently unable to identify pathogenic organisms in patients with meningitis, despite the clear purulence of the resulting samples ( 12 ). Therefore, there is great interest in using culture-independent, DNA-based methods for pathogen identification in CSF samples ( 12 , 13 ). In this study, we found that the nearly consistent low bacterial abundances relative to the contamination levels of reagents greatly diminish the utility of molecular approaches, even with the inclusion of rigorous controls and computational removal of contaminant sequencing reads, regardless of how the samples are processed or extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Some possible candidates include nucleic acid amplification assays, CSF cytokines (interleukin-6), CSF lactate, or CSF procalcitonin, which have had variable results in the literature so far [ 26–30 ]. 16S rRNA has had a number of studies evaluating its diagnostic value, and it may be of use for culture-negative suspected iERIs [ 31 , 32 ]. Future research could also include work on developing and validating scoring systems, diagnostic trees [ 11 ], or predictive algorithms, which have previously been found to have high accuracy in differentiating between bacterial and viral meningitides [ 33 ].…”
Section: Discussionmentioning
confidence: 99%